Effect of physical exertion training on bio-kinetic abilities in weightlifting among students of Physical Education and Sports Sciences - Mukheef , Salih Mahdi; Mahdi , Mustafa Salih (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The objective of this research was to study the effect of physical exertion training on bio-kinetic abilities in weightlifting among students of Physical Education and Sports Sciences. The present study had a pre-posttest experimental design in which participants were recruited in two groups: experimental group and control group. A total of 30 students of Physical Education and Sports Sciences constituted the sample of the study. The sample selection was done by a comprehensive inventory method. Participants were equally allocated into two groups with n=15 in each group. Participants of experimental group were made to perform special physical exercises with three training units per week during eight weeks. The statistical analysis was carried out using SPSS. The results of the study showed that the physical exertion training has a positive effect on developing some bio-kinetic abilities in weightlifting among first-year students of Physical Education and Sports Sciences.